Studi Kasus Perang Saudara di Yugoslavia pada Tahun 1991 - 1992 Ditinjau dari Aspek Hukum Humaniter dan HAM serta Manfaatnya bagi TNI Angkatan Laut - Wicaksono, Isa Agung; Prawiro, Suharno; Achmad, Achmad (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This study aims to analyze the civil war that occurred in Yugoslavia between 1991 and 1992, focusing on the perspective of humanitarian law and human rights (HAM). The war involving various ethnic groups had a major impact on civil society and challenged the application of humanitarian law principles, such as protection of civilians and limitations on the use of force in conflict. This study also explores the implications of the civil war on international policy and the role of the Indonesian Navy, especially in implementing the principles of humanitarian law and human rights in the context of military operations abroad. Through a case study approach, this study is expected to provide a deeper understanding of the importance of strengthening the capabilities of the Indonesian Navy in dealing with armed conflict situations while still prioritizing the protection of human rights and international humanitarian law. The benefits of this study can be a reference for improving the training and readiness of Indonesian navy troops in facing international peacekeeping tasks in the future. when viewed from humanitarian law and human rights, namely the existence of an educational aspect, one of which is the importance of the role of diplomacy for the Indonesian Navy in accordance with the role carried out in efforts to maintain peace and defense and security cooperation, especially at sea as part of national diplomacy. The existence of an inspirational aspect, one of which is the need for peace values ??and maintaining good relations and establishing cooperation in regional and global environments to avoid war by seeking diplomatic functions and the existence of an instructive aspect, one of which is that International Humanitarian Law and Human Rights must be a guideline for every Indonesian Navy soldier in carrying out their duties, especially officers and commanders in the Unit.